Novel hyaluronic acid–methotrexate conjugate suppresses joint inflammation in the rat knee: efficacy and safety evaluation in two rat arthritis models. Issue 1 (December 2016) - Tamura, Tatsuya; Higuchi, Yoshinobu; Kitamura, Hidetomo; Murao, Naoaki; Saitoh, Ryoichi; Morikawa, Tadashi; Sato, Haruhiko
Abstract Background Methotrexate (MTX) is one of the most widely used medications to treat rheumatoid arthritis (RA), and recent studies have also suggested the potential benefit of the drug for the treatment of osteoarthritis (OA) of the knee. MTX is commonly administered in oral formulations, but is often associated with systemic adverse reactions. In an attempt to address this issue, we have shown previously that a conjugate of hyaluronic acid (HA) and MTX exhibits potential as a drug candidate for intra-articular treatment of inflammatory arthritis. In this study, we compare the efficacy and safety of an optimized HA-MTX conjugate, DK226, with that of MTX in inflammatory arthritis rat models. Methods In vitro activity of DK226 was assessed in human fibroblast-like synoviocytes (HFLS) and a synovial sarcoma cell line, SW982. Release of MTX from DK226 was investigated after incubation with rabbit synovial tissue homogenate or synovial fluid. In vivo efficacy of DK226 was evaluated in antigen-induced arthritis (AIA) and collagen-induced arthritis (CIA) in the rat knee. Pharmacokinetics and hematological toxicity after treatment with oral MTX or an intra-articular injection of DK226 were compared in AIA. Results Proliferation of HFLS and SW982 cells was inhibited by DK226, and the inhibitory activity was reversed by cotreatment with excess HA or anti-CD44 antibody. MTX was released from DK226 by incubation with rabbit synovial tissue homogenate or synovial fluid at pH 4.0, but not at pH 7.4. AIA was ameliorated by intra-articular DK226, but not by HA, as potently as oral MTX. Hematological toxicity was induced by oral MTX, but not by DK226. The maximum plasma concentration of MTX after oral MTX was 40 times higher than the concentration of MTX after an intra-articular injection of DK226. Knee swelling in AIA was inhibited by intra-articular injections of DK226, but not by free MTX or a mixture of HA and MTX. In CIA, an injection of DK226 into the right knee joint significantly reduced swelling and synovial inflammation of the treated knee joint, but had no effect on the untreated contralateral knee joint. Conclusions DK226 exerted anti-arthritic effects in two different models of arthritis. The conjugate had a wider therapeutic window than oral MTX, and could be a future drug for treatment of arthritic disorders, including inflammatory OA.